Talazoparib plus enzalutamide in men with HRR-deficient metastatic castration-resistant prostate cancer: final overall survival results from the randomised, placebo-controlled, phase 3 TALAPRO-2 trial - Fizazi, Karim; Azad, Arun A; Matsubara, Nobuaki; Carles, Joan; Fay, André P; De Giorgi, Ugo; Young Joung, Jae; Fong, Peter C C; Voog, Eric; Jones, Robert J; Shore, Neal D; Dunshee, Curtis; et al. (The lancet, 2025)
Background - Metastatic castration-resistant prostate cancer remains incurable and is particularly aggressive in patients with alterations in DNA damage repair genes involved directly or indirectly in homologous recombination repair (HRR). In the primary analysis of TALAPRO-2, talazoparib plus enzalutamide significantly improved radiographic progression-free survival (rPFS) versus enzalutamide plus placebo in patients with metastatic castration-resistant prostate cancer harbouring HRR gene alterations. At primary analysis, overall survival was immature. Here we report final prespecified overall survival analysis, updated rPFS, safety, and patient-reported outcomes in the HRR-deficient cohort of TALAPRO-2. - Methods - TALAPRO-2 is an ongoing international, randomised, double-blind, placebo-controlled phase 3 trial. The HRR-deficient cohort included randomly assigned patients from 142 hospitals, cancer centres, and medical centres in 26 countries; the study included men aged at least 18 years (≥20 years in Japan) with asymptomatic or mildly symptomatic metastatic castration-resistant prostate cancer, progressive disease at study entry, and no previous life-prolonging systemic therapy for castration-resistant prostate cancer, but were receiving ongoing androgen deprivation therapy. Patients were prospectively assessed for tumour HRR gene alterations and randomly assigned (1:1) to once-daily oral talazoparib 0·5 mg plus enzalutamide 160 mg or enzalutamide plus placebo stratified by prior treatment (yes vs no) for castration-sensitive disease. The sponsor, patients, and investigators were masked to talazoparib or placebo, whereas enzalutamide was open label. The primary endpoint was rPFS (time from randomisation to radiographic progression or death, whichever occurred first) by blinded independent central review, and overall survival (time from randomisation to death due to any cause) was a key alpha-protected secondary endpoint, both assessed in the intention-to-treat population. Follow-up for overall survival was intended to continue until the planned final analysis. For statistical significance at the final overall survival analysis, the two-sided p value from the stratified log-rank test needed to be 0·024 or less based on a group sequential design with O'Brien-Fleming spending function. Safety was assessed in patients who had received at least one study drug dose. The trial is registered with ClinicalTrials.gov, NCT03395197. - Findings - Between Dec 18, 2018, and Jan 20, 2022, 399 patients with HRR-deficient metastatic castration-resistant prostate cancer were randomly assigned (200 [50%] to talazoparib plus enzalutamide and 199 [50%] to enzalutamide plus placebo). At a median follow-up of 44·2 months (IQR 36·0-50·8), treatment with talazoparib plus enzalutamide resulted in a statistically significant improvement in overall survival versus enzalutamide (hazard ratio [HR] 0·62 [95% CI 0·48-0·81]; two-sided p=0·0005); median overall survival 45·1 months (95% CI 35·4-not reached) in the talazoparib group versus 31·1 months (27·3-35·4) in the control group. In the subgroup of patients with BRCA1/2 alterations (n=155 [39%]), median overall survival was not reached for talazoparib plus enzalutamide versus 28·5 months for enzalutamide (HR 0·50 [95% CI 0·32-0·78]; p=0·0017); 4-year overall survival rates were 53% in the talazoparib group versus 23% in the control group. In patients without BRCA1/2 alterations (n=244 [61%]), median overall survival was 42·4 months for talazoparib plus enzalutamide versus 32·6 months for enzalutamide (HR 0·73 [95% CI 0·52-1·02]; p=0·066). Updated rPFS favoured talazoparib plus enzalutamide versus enzalutamide (HR 0·47 [95% CI 0·36-0·61]; p<0·0001; median rPFS 30·7 vs 12·3 months). No new safety signals were identified; most common adverse events of grade 3 or higher with talazoparib plus enzalutamide were anaemia (86 [43%] patients) and neutropenia (39 [20%] patients). - Interpretation - Talazoparib plus enzalutamide resulted in statistically significant and clinically meaningful improvement in survival versus enzalutamide plus placebo, further supporting this combination as a standard of care in HRR-deficient metastatic castration-resistant prostate cancer. - Funding - Pfizer.
Online verfügbar: 16. Juli 2025, Artikelversion: 31. Juli 2025
Gesehen am 21.01.2026